An Imaging Surface Plasmon Resonance Biosensor Assay for the Detection of T-2 Toxin and Masked T-2 Toxin-3-Glucoside in Wheat - Md Zakir Hossain; Susan P. McCormick; Chris M. Maragos (Toxins, 2018)
A sensitive, rapid, and reproducible imaging surface plasmon resonance (iSPR) biosensor assay was developed to detect T-2 toxin and T-2 toxin-3-glucoside (T2-G) in wheat. In this competitive assay, an amplification strategy was used after conjugating a secondary antibody (Ab2) with gold nanoparticles. Wheat samples were extracted with a methanol/water mixture (80:20 v/v), then diluted with an equal volume of primary antibody (Ab1) for analysis. Matrix-matched calibration curves were prepared to determine T-2 toxin and T2-G. Recovery studies were conducted at three spiking levels in blank wheat. Mean recoveries ranged from 86 to 90%, with relative standard deviations for repeatability (RSDr) of less than 6%. Limits of detection were 1.2 ng/mL of T-2 toxin and 0.9 ng/mL of T2-G, equivalent to their levels in wheat, of 48 and 36 µg/kg, respectively. The developed iSPR assay was rapid and provided enough sensitivity for the monitoring of T-2 toxin/T2-G in wheat. This is the first iSPR assay useful for detecting the “masked” T2-G in wheat.